225k views
5 votes
Please help I need step by steps with this!!

Please help I need step by steps with this!!-example-1
User Patonz
by
6.0k points

1 Answer

7 votes

Answer:

x=2, y=-5

Explanation:

3x+2y=-4

4x-y=13

Let's subtract 4x from both sides of the second equation, and then multiply both sides by -1:

y=4x-13

Now that you have isolated y, you can plug it into the first equation:

3x+2(4x-13)=-4

3x+8x-26=-4

11x=22

x=2

y=-5

Hope this helps!

User Tukaram Patil Pune
by
5.1k points